Imobilização de nanopartículas de ouro em filmes automontados como sensores de íons cadmio e cobre - de Almeida, Jéssica Cristina (2018)
Nowadays, with industrial development, the concentrations of toxic materials produced and dumped by factory and domestic waste are increasing. The heavy metals are part of these contaminants which currently contaminate soil and groundwater, threatening the health of all living creatures. For this reason, the environmental monitoring of these metals is increasingly relevant. This work evaluated the development of electrochemical sensors in different architectures and materials, aiming at the detection and quantification of cadmium (Cd) and copper (Cu) metals in contaminated water sources. These electrochemical sensors were constructed by the Layer by Layer (LbL) technique. The LbL uses opposite charge solutions to form self-assembled layers of nanometric thickness by spontaneous adsorption on solid substrates. Sodium montmorillonite clay (MMT-Na +) and b-cyclodextrin (b-CD) are materials whose structure provides adsorption capacity of metal ions. Therefore, they were selected to be immobilized in the self-assembled films. Besides these materials, will also be tested the use of gold nanoparticles (AuNPs) to verify the improved sensitivity to the analytes. These AuNPs were synthesized in two shapes: nanospheres (AuNEs) and nanoroads (AuNBs). In this way, films were constructed in the (PAH/MMT)10, AuNEs/MMT)10, (AuNBs/MMT)5 and (PAH/b-CD)5 architectures. The self-assembled films were characterized by spectroscopic and voltammetric analyzes, to verify the growth of their layers and their detection efficiency through the Cd and Cu metals in solution. The electrochemical responses for all tested architectures were successfully obtained. The films built with MMT-Na+ clay presented potential for quantification of metals in wastewater, according to the standards established by the Environment National Council (CONAMA). However, the results obtained at the detection of metallic ions by the b-CD films were more sensitive, allowing the quantification of metals in the maximum permitted concentrations for drinking water according to the guidelines of the World Health Organization (WHO).